Intervención social en el abordaje y prevención de conductas de discriminación y violencia en adolescentes - Carrión María, M. Carmen (Cuadernos de Trabajo Social, 2010)
Violent and discriminatory conducts in teenagers and young people represent a social problem whose impact seems to maintain a certain tendency to increase. In this article the state of matter is examined referring to the expressions of the conducts with a higher impact and seriousness among young people. Then we relate them to the concept of Authoritarian attitude. Next, an analysis of the explanatory variables is presented, and some reflections for the social intervention in the approach and prevention of them are proposed.
Keywords: Violence; Discrimination; Teenagers; Authoritarian; Attitude; Social intervention